Implementation of participatory sensing approach in mobile vehicle based sensor networks - Mednis, Artis (My University, 2013)
In this paper author describes his research with the goal to develop and experimentally verify specific data recording and processing methodologies based on participatory sensing approach implementation in mobile vehicle based sensor networks. To reach this goal, author performed study of literature, testing of hypothesis using general purpose computer devices, adaptation of smartphones for participatory sensing, development of special purpose embedded devices, practical experiments with selected technical equipment and software as well as gathering of experimental results and following statistical analysis. The result of this research are several data acquisition and processing methodologies based on participatory sensing approach and mobile vehicle based sensor networks as well as evaluation of these methodologies.
Keywords: participatory sensing; mobile sensor networks; methodologies; microphones; accelerometers